Fig. 5 in Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica - Matsubayashi, Makoto; Tsuchida, Sayaka; Kobayashi, Atsushi; Shibahara, Tomoyuki; Nakamura, Hiroshi; Murata, Koichi; Ushida, Kazunari (Zenodo, 2018)
Fig. 5. Composite line drawing of oocyst of Eimeria raichoi n. sp (previously referred as type B). Scale bars indicate 10 μm. Published as part of Matsubayashi, Makoto, Tsuchida, Sayaka, Kobayashi, Atsushi, Shibahara, Tomoyuki, Nakamura, Hiroshi, Murata, Koichi & Ushida, Kazunari, 2018, Molecular identification of two Eimeria species, E. uekii and E. raichoi as type B, in wild Japanese rock ptarmigans, Lagopus muta japonica, pp. 243-250 in International Journal for Parasitology: Parasites and Wildlife 7 (3) on page 249, DOI:10.1016/j.ijppaw.2018.06.005, http://zenodo.org/record/13135846